IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM MATERI PENDIDIKAN AGAMA ISLAM DI SMP QUBA KOTA SORONG PROVINSI PAPUA BARAT - Fitriani, Ely (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Islamic religious educationn learningg thatt is linkedd too thee existing diversityy (directly), whetherr itt is ethnic diversity, language, race, ethnicity, anddsooon. Thissis doneebecause we cannot avoid that we encounter many public schoolssinnoneeclasssconsistinggoff very diverse students, some with different ethnicities, languages, ethnicities, and so on. The purpose of this study is to describe the form of multicultural education in Islamic religious education materials and also how the value of what has been implemented into Islamic religious education materials at Quba Middle School Sorong City. This study uses qualitative data. Research data obtained through observation, interviews, and documentation. The data analysis technique used is content analysis and qualitative descriptive, which aims to describe the situation or want to know a certain phenomenon. The results showed that the Quba Middle School in Sorong City had implemented multicultural education in Islamic education materials. The implementation is through the addition of themes or incorporating multicultural values in Islamic religious education materials that already exist at the Quba Junior High School in Sorong City, and the teaching is carried out in a thorough and in-depth way